Efficient Signalling with Dividends and Investments - Ambarish, Ramasastry.; John, Kose; Williams, Joseph (Journal of Finance, 1987)
An efficient signalling equilibrium with dividends and investments or, equivalently, dividends and net new issues of stock is constructed, and its properties are identified. Because corporate insiders can exploit multiple signals, the efficient mix must minimize dissipative costs. In equilibrium, many firms both distribute dividends and deviate from first-best investment. Also, the impact of dividends on stock prices is positive. By contrast, the announcement effect of new stock is negative for firms with private information primarily about assets in place and positive for firms with inside information mainly about opportunities to invest.